The Effect of Tribal Identity on Youth Political Participation in Karak Governorate - Tarawineh, Raafat; al bahri, Nessren; Al-Sarayrah, Ali; Jaber, Areej; Al Tarawneh, Anas (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to examine the impact of tribal identity on youth political participation in Al-Karak Governorate. Methods: The study utilized a descriptive-analytical approach. The population consisted of 316,629 individuals in Al-Karak Governorate, from which a cluster random sample of 2,988 participants was selected, including 1,092 males and 1,896 females. A validated and reliable questionnaire was distributed to the sample. Results: The results showed that Jordanian youth in Al-Karak perceive tribal identity at a high level, while their political participation was rated at a moderate level. Tribal identity was found to influence youth political participation in the governorate, with dimensions of tribal identity accounting for 76.5% of the variation in overall youth political participation. Conclusion: The study recommends implementing awareness initiatives to encourage youth to overcome the negative aspects of tribal identity and addressing youth issues comprehensively to establish a foundation for genuine citizenship that transcends allegiance to specific groups or factions.